The Relationship Between Social Support Of Coolers And The Self Adjustment Of Employees With The Deaf : Hubungan Antara Dukungan Sosial Rekan Kerja Dengan Penyesuaian Diri Karyawan Penyandang Tunarungu - Tri Hendrayanti; Dwi Nastiti (Universitas Muhammadiyah Sidoarjo, 2021)
This research was conducted because there is a phenomenon of adjustment problems for deaf employees in their workplace, PT. Young Tree Industry Sidoarjo. The purpose of this study was to determine the relationship between the social support of coworkers and the adjustment of deaf employees at PT. Young Tree Industry Sidoarjo. This research is a correlational quantitative research. The population of deaf employees is 23 people so that all of them are used as research samples. The data collection technique uses a psychological adjustment scale and social support which is arranged on a Likert scale. The data analysis technique for hypothesis testing was carried out with the Pearson Correlaton Product Moment. The results of this study indicate the correlation coefficient (rxy) = 0.834 (significance 0.000 <0.05). Thus the research hypothesis is accepted, that there is a positive relationship between co-workers' social support and adjustment to deaf employees at PT. Young Tree Sidoarjo. This means that the higher the social support, the higher the adjustment, and vice versa. The determination test shows the effect of social support on self-adjustment by 68%.